The student's experience as an opportunity or didactic obstacle? Analysis of the oral and written narratives of the students in the History, Geography and Social Sciences class - Soto Yonhson, Andrés (Universidad Nacional del Litoral, 2019)
This article aims to socialize the didactic problem that arose in the preparation of the Master's thesis in Didactics of History and Social Sciences at the Alberto Hurtado University, Chile. On this occasion, oral and written narratives that students from middle third in a paid private school in Santiago de Chile made in History, Geography and Social Sciences classes will be analyzed. This sought to characterize the relationship between the development of historical thinking and the individual and social experience of students, all in order to identify the challenges and educational opportunities for teaching and learning historical discipline. From the previous analysis it was concluded that there is a distance between the experiences of the students and the different instances of the teaching-learning process of History, which has as a consequence that the experiential becomes a didactic obstacle and not an element from which to work in the classroom.